The influence of store image on customer satisfaction: case study of Pemasaran Melaka Sdn. Bhd. / Nur Fatin Farhana Roslan and Nur Hazirah Hasri - Roslan, Nur Fatin Farhana; Hasri, Nur Hazirah (2014)
Pemasaran Melaka Sdn Bhd is a company that market Melaka products. During the first few years of its establishment, the customer accepted Pemasaran Melaka positively by the local authority. This can be indicated when many local entrepreneur want to supply the product in Pemasaran Melaka and the monthly sales by Pemasaran reached RM100k – RM200k. In the recent years, the sales by Pemasaran Melaka were slightly reduced. According to managing director of PMSB, this could due to the decreasing level of customer satisfaction towards store image at PMSB compared to when it was first established. Thus, this research is to study the influence of Pemasaran Melaka store image on customer satisfaction. The objectives of this study is to determine the element of store image conducted by PMSB that influence customer satisfaction, to rank the store image element, to examine the element of store image towards level of customer satisfaction and to give the recommendation to the company on what most effective element of store image they can use in time to come. In this study, the researcher design, descriptive, exploratory and conclusive research had been used. For the sampling technique, convenience sampling has been used where the researcher will distribute 100 questionnaires to customer of PMSB. Reliability test, frequency analysis, pearson correlation and multiple regression had been used in this study to get the data from the questionnaire. The findings showed service quality is the most effective element while product assortment is the least effective tool. The research also provides some recommendation to PMSB to improve their store image to become more effective. All the data gathered from the questionnaire has been analyzed using Statistic Package for Social Science (SPSS) version 20.0.